Symptoms perception and pre-hospital care seeking behaviour and its influence towards outcome of patients with acute coronary syndrome in emergency medicine department, Hospital Universiti Sains Malaysia - Annuar, Wan Masliza Wan Mohd (2013)
Good coronary care begins from the patient's home including early decision to seek medical attention. As such, it is recommended that the patients activate ambulances, rather than to use their own transportations to reach the hospitals. It is not known whether our Malaysian patients prefer to use private transportations or ambulances when they develop chest pain. This study aims to explore this research question. To explore 1) the patients’ interpretation regarding the symptoms they are experiencing -heart attack or other condition. 2) To determine the time delay between onset of symptoms to the activation of EMS or using own transportation to Emergency Department Elospital Universiti Sains Malaysia (HUSM). 3) To determine the patients’ preference of mode of transportation and the reason for it This is a cross-sectional study using open labeled structured questionnaire on patients diagnosed with acute coronary syndrome (ACS) in the emergency department of Hospital Universiti Sains Malaysia from June 2012 to November 2012. Out of the 110 patients surveyed, 105 (95.5%) patients chose to use own transportation when they developed symptoms suggestive of ACS. Only 3 patients (2.7%) came to the emergency department within 1 hour of onset, and all these 3 patients chose to use ambulances as their modes of transportation. None of the patients who chose own transportation came within the first hour of symptoms onset. This is shown to 0.001). The be statistically significant (p level of education as well as past history of ischemic heart disease did not significantly influence the patients’ choice of transportation. Overall, the awareness of symptoms of acute coronary syndrome is still poor. The extremely low percentage of patients choosing ambulances shows that there is a lot more educational work to be done to educate our community on acute coronary syndrome.